KOMPETENSI GURU MADRASAH IBTIDAIYYAH DALAM PEMBELAJARAN SAINS BERBASIS PENDIDIKAN KARAKTER - Mukhlis Fatchurrohman (MAMBA'UL 'ULUM, 2019)
This article reviews the importance of the competency of Elementary School or Islamic Elementary School Teachers in instruction of science subject. Learning science of elementary school teacher, in teaching science, should master instruction and teaching of science as well as its assessment technique, so that the students can achieve a determined indicator. From this article, it is found a conclusion that the standard of the successful teacher depends on the teacher’s personality, the mastery of teaching method, the teacher’s frequency and intensity of interaction with students and the mastery of instructional strategy.